Peningkatan Keterampilan Menulis Teks Rekon Menggunakan Media Series Of Pictures - Ardania, Ardania; Idawati, Idawati; Anwar, Anwar (TITIK DUA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2025)
This study aims to describe the improvement of recount text writing skills of Class IX students of SMPNegeri 1 Makassar by using Series of Pictures media. This type of research is Classroom Action Research. The population of this study was students of class IX.1 SMP Negeri 1 Makassar, totaling 40 students. Research data were obtained during the planning, action implementation, observation, and reflection stages through tests, classroom observation, and documentation. The tests carried out included initial tests, cycle I tests, and cycle II tests. The instruments used in this study included short story text writing skill test questions, analysis sheets, observation sheets, and documentation guides. The research data were analyzed using qualitative and quantitative approaches. The results showed that in Cycle I, students who did not reach the completion were 20 people, or 50%, while in Cycle II, students who did not reach the completion were only 8 people, or 20%. After cycle II, student completeness was 80%, or 32 people. So, it can be said that using Series of Pictures media in teaching how to write recount texts in cycle II successfully helped improve the writing skills of students in class IX.1 at SMP Negeri 1 Makassar.